STRATEGI OPTIMALISASI LAYANAN DIFABEL PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA YOGYAKARTA - Mareta Prameshwari, Valla; Awal Satrio Nugroho, Muhammad; zulkifli (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
Disability services are an obligation mandated by Indonesian Constitution to ensure equal access to public services for all citizens without exception, including for citizens who have physical, mental, intellectual and sensory limitations (disabled). However, in practice, the provision of disability-friendly public services is still not optimal, in terms of utilization and provision of existing facilities. It is this urgency that directs research towards the aim of knowing the factors that cause less optimal services for people with disabilities to formulate effective strategies in order to optimize services. This research belongs to the type of qualitative research with descriptive analysis. The analytical tool used to formulate effective strategies is SOAR analysis. SOAR Analysis is a development of SWOT Analysis which focuses on leveraging organizational strengths and opportunities to realize aspirations and results that are explored together to present more optimistic strategies, rather than focusing on weaknesses and threats. It is very much suitable for the organizational form of government agencies; those prioritize public trust. The results of the study show that factors causing the non-optimal disability services in Office of Yogyakarta City Library and Archives are facilities and infrastructures, human resources (HR), and policies. The strategy for optimizing DPK Yogyakarta City disability services consists SA Strategy (operating disabled service attendants), SR Strategy (development of voice book search feature and voice archive search feature), OA Strategy (installation of induction loop system in service areas, providing wheelchairs, educational film collections with sign language, adding PCs, media transfer tools, talking books, and also replacing damaged mobile fleets to re-function mobile library for Special Needs Schools), and OR Strategy (organizing Applied Literacy activities involving disabled and launching archival search services and special archive restoration services for disabled in near future).